1993
DOI: 10.5014/ajot.47.9.811
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Occupational Therapy Intervention on Mothers of Children With Cerebral Palsy

Abstract: Using the interviewing techniques and ethnographic methodology reported by Hinojosa, we explored the relationships between mothers of preschool children with cerebral palsy and their children's occupational therapists. Data from two interviews with five mothers were transcribed, organized into topics, and, through constant comparative analysis, formulated into themes. One theme, "Is anybody listening?" suggested that professionals often disregard information provided by the mothers; a second theme, "Not anothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1
3

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 7 publications
1
21
1
3
Order By: Relevance
“…Others used descriptors such as personable, understanding, appreciative, open and respectful, all o f which suggest a positive social relationship. These findings are supported by Washingtonand Schwartz (1996),Case-Smith and Nastro (1993), andHinojosa (1990), physical and occupational therapist researchers who reported parents' valuation o f the social relationship support developed with their child's therapist. Perhaps this parental valuation can also be interpreted as parents viewing therapists as mentors.…”
supporting
confidence: 54%
See 2 more Smart Citations
“…Others used descriptors such as personable, understanding, appreciative, open and respectful, all o f which suggest a positive social relationship. These findings are supported by Washingtonand Schwartz (1996),Case-Smith and Nastro (1993), andHinojosa (1990), physical and occupational therapist researchers who reported parents' valuation o f the social relationship support developed with their child's therapist. Perhaps this parental valuation can also be interpreted as parents viewing therapists as mentors.…”
supporting
confidence: 54%
“…These are just a few comments that punctuate the critical between client and self as well as mindfulness o f who the "expert" is. It could also inhibit relationship building, which has been shown to be important for mothers (Case-Smith & Nastro, 1993;Washington & Schwartz, 1996). Language may suggest ownership o f meaning and therefore jargon usage during parent interviews may suggest that, rather than being characteristic o f dualism (Perry, 1981) Once alternative wording was provided, they responded with descriptions o f the therapist being "open," "honest," "straightforward," "makes me comfortable," and "caring toward the child."…”
Section: Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Families have identified characteristics that define high quality early intervention service providers as good listeners and communicators (Blue-Banning, Summers, Frankland, Nelson, & Beegle, 2004;Case-Smith & Nastro, 1993;Dinnebeil, Hale, & Rule, 1999;Washington & Schwartz, 1996) and individuals who demonstrate sensitivity to children, provide individual attention to their child, follow through with ideas, and have a willingness to ignore the clock during therapy sessions (McWilliam, Young, & Harville, 1996). In addition to these characteristics, parents report that it is important for service providers to have technical knowledge and skills (Wehman & Gilkerson, 1999), involve families in their children's learning, focus on their child's strengths (Dinnebeil et al, 1999;Viscardis, 1998), fit therapy into family daily routines and activities (Brotherson & Goldstein, 1992;Edwards, Milland, Praskac, & Wisniewski, 2003), use technology as part of intervention (Brotherson & Goldstein, 1992), and include siblings in therapy sessions (Thompson, 1998).…”
Section: Mismatch With Consumer Perspectivesmentioning
confidence: 99%
“…19 Welldeveloped communication skills of professionals providing care for children with disabilities, such as information sharing and listening were also mentioned. 19,20,23,25 Roelofsen et al 36 reported improvements on 13 aspects of team functioning in one or more teams after having implemented their newly developed Children's RAP, a rehabilitation activities profile for children. The tool enhanced communication by eliciting explicitly formulated goals, comprehensive reports, categorization of information and transparent delineations of the roles of the various members during the team meetings.…”
Section: Communicationmentioning
confidence: 99%